A qualitative exploration of the experiences of primary care patients engaged in email counseling meant to increase physical activity - Tomas Vetrovsky; Klaudia Vetrovska; Vaclav Bunc (Palacký University Olomouc, 2019)
Background: As insufficient physical activity is a widespread public health problem, the patients' perspective and experiences during their efforts to increase levels of physical activity need to be explored and elucidated. Objectives: The purpose of our study was to qualitatively analyze the patient-written email messages in order to explore patients' experiences during a 12-week pedometer-based physical activity intervention in a primary care setting that was paired with email counseling. Methods: The content of 31 email messages from 10 participants was extracted, coded, and analyzed using thematic analysis. Results: We identified 22 themes that were grouped into 3 categories: reflections on the pedometer-based intervention, use of behavior change techniques, and barriers that affected participants' engagement in physical activity. We have also anecdotally described several interesting aspects of behavior change techniques: negative attitudes elicited by the goal setting process, learning from their own data, and enjoyment associated with self-monitoring. Conclusion: Qualitatively analyzing email messages written as part of the physical activity counseling process is useful in documenting patients' perceptions and use of different behavior change techniques and their reported barriers that get in the way of increasing their physical activity.